Ketertindasan Masyarakat Melayu Riau dalam Bulan Kabut dan Sengketa Tanah Ulayat - marlina, marlina (METASASTRA: Jurnal Penelitian Sastra, 2018)
The research aims to uncover condition of forest and community in Riau caused by annual forest fires disaster found in short stories of M. Badri’s “Bulan Kabut” and Sy. Bahri Judin’s “Sengketa Tanah Ulayat”.  It is a descriptive qualitative research applying socio-literary approach. The data taken in the short stories and community were described and analyzed. Based on the analysis of the two short stories, it can be concluded that both of M. Badri’s and Sy.Bahri Judin’s short stories describe the real condition of forest and community in Riau. The community has lost the  forest as well as communal reserved land and obtained negative impact of annual forest fires in Riau. Both short stories are intended to criticize government and plantation companies  that are regarded to be responsible for forest fires and taking over communal reserved land from Riau community.